A STUDY OF THE CONTRIBUTION ON SHALYA TANTRA WITH SPECIAL REFERENCE TO CHARAK SAMHITA (AYUSHDHARA, 2017)
Ayurveda has been created by lord Brahma and descended to earth in the form of Trisutra. This get ramified into Astanga Ayurveda (8 branches of Ayurveda). The 8 branches are Kayachikitsa, Shalakya tantra, Shalya tantra, Vishgarvairodhik prashaman, Bhoot vidya, Kaumarbhritya, Rasayana and Vajikaran. Shalya tantra which is one of the branches of Astanga ayurveda is defined as the branch of Ayurveda which describes the methods of removal of different kinds of foreign object such as grass, wood, stone, sand, metal, bone, hair and nails, pus, exudation, vitiated ulcers, use of caustic alkalies, fire and diagnosis of ulcers and wounds. Charak samhita though deals or covers all the 8 branches of Astanga Ayurveda but it emphasis more on Kayachikitsa. Shaya tantra is more elaborately and nicely dealt by the father of surgery Sushruta in his Sushruta samhita text. The Shalya related topics are all scattered in Charak samhita and make it hard for the readers to find out their topics. So, for the convenience of the reader and to make it updated with the changing present era and easily accessible and handy, the present work has been carried out. In total 27 chapters of Charak samhita has Shalya related topics. 10 chapters of Sutrasthana, 1 chapter of Shaarer sthana and 16 chapters of Chikitsa sthana has Shalya related topics. Compiling the scattered topics of Shalya available in Charak samhita will make the reader easy to choose its topic of interest in Charak samhita regarding the Shalya related topics.